Towards Fish Lipid Nutrigenomics: Current State and Prospects for Fin-fish Aquaculture - Leaver, Michael; Bautista, Jose M; Björnsson, Björn Thrandur; Jönsson, Elisabeth; Krey, Grigorios; Tocher, Douglas R; Torstensen, Bente E (Reviews in Fisheries Science, 2008)
Lipids are the predominant source of energy for fish. The mechanisms by which fish allocate energy from lipids, for metabolism, development, growth and reproduction are critical for understanding key life history strategies and transitions. Currently, the major lipid component in aquaculture diets is fish oil (FO), derived from wild capture fisheries that are exploited at their maximum sustainable limit. The increasing demand from aquaculture for FO will soon exceed supply and threaten the viability of aquaculture. Thus, it is essential to minimize FO use in aquaculture diets. This might be achieved by a greater understanding of lipid storage and muscle growth, or the identification of alternatives to FO in feeds. This review focuses on recent research applying molecular and genomic techniques to the study of fin-fish lipid metabolism from an aquaculture perspective. Accordingly, particular emphasis will be given to fatty acid metabolism and to highly unsaturated fatty acid (HUFA) biosynthesis, and to the transcriptional mechanisms and endocrine factors that regulate these processes in fish. Comparative studies of gene function and distribution are described which, when integrated with recent fish genome sequence information, provide insights into lipid homeostasis and the outcomes associated with the replacement of FO in fish diets.